Study of genetic variability, heritability, and genetic advance for yield-related traits in tomato (Solanum lycopersicon MILL.) - Rasheed, Adnan; Ilyas, Muhammad; Khan, Taj Naseeb; Mahmood, Athar; Riaz, Usama; Chattha, Muhammad Bilal; Al Kashgry, Najla Amin T.; Binothman, Najat; Hassan, Muhammad Umair; Wu, Ziming; Qari, Sameer H. (Frontiers in Genetics, 2023)
Tomato is one of the most significant vegetable crops, which provides several important dietary components. Pakistan has a significantly low tomato yield compared to other countries because of low genetic diversity and the absence of improved cultivars. The present study aimed to investigate the genetic variability, heritability, and genetic advance for yield and yield-related traits in tomato. For this purpose, eight tomato parents and their fifteen crosses or hybrids were evaluated to study the relevant traits. Significant variation was observed for all studied traits. Higher values of genotypic coefficient of variability (GCV) and phenotypic coefficient of variability (PCV) were recorded for yield plants-1 (YP) (37.62%, 37.79%), and the number of fruits cluster-1 (NFRC) (31.52%, 31.71%), which indicated the selection for these traits would be fruitful. Higher h2 estimates were observed for number of flowers cluster-1 (NFC) (0.99%), single fruit weight (SFW) (g) (0.99%), and yield plant-1 (YP) (kg) (0.99%). Single fruit weight (SFW) exhibited higher values of all components of variability. High genetic advance as % of mean (GAM) coupled with higher heritability (h2) was noted for yield plant-1 (YP) (52.58%) and number of fruits cluster-1 (NFRC) (43.91). Among the fifteen hybrids, Nagina × Continental was selected as high yielding hybrid (3kg) for further evaluation and analysis. These results showed that superior screening hybrids could enhance tomato seed production, indicating a large amount of genetic variation among the parents. Further studies should be conducted to check the yield stability of these hybrids as well as their suitability for varietal development.